Trade Union Relationship with Corporate Management - Tini Mogea (Journal of Management and Social Sciences, 2023)
The need to manage a good and coordinated relationship among employees is critical in human resource management. In order to achieve organizational goals, the relationships between individuals involved in the context must be well managed, especially if the context is broader and involves a union. This brief article will focus on the relationship within the union. The fundamental question here is, "How is the working relationship between the union and the company management?" This question's response elaborates on six main points. First, we'll talk about the nature of trade unions and the issues they face, including in Indonesia. Second, several factors contributing to the decline in union membership will be identified. Third, labor and trade union regulations will be explained. The fourth topic will be the stages of the union process. Fifth, the collective bargaining agreement will be discussed. The complaint procedure will be described in the sixth section.